2001
DOI: 10.1046/j.1365-2249.2001.01561.x
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of circulating HBcAg-specific CD8 T cells in hepatitis B infection: a flow cytometric analysis

Abstract: SUMMARYViral antigen-specific T cells are important for virus elimination. We studied the hepatitis B virus (HBV)-specific T cell response using flow cytometry. Three phases of HBV infection were studied: Group A, HBeAg (1) chronic hepatitis; Group B, HBeAb (1) HBV carrier after seroconversion; and Group C, HBsAb (1) phase. Peripheral T cells were incubated with recombinant HB core antigen (HBcAg), and intracytoplasmic cytokines were analysed by flow cytometry. HBcAg-specific CD4 and CD8 T cells were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…However, in contrast to observations in murine systems, we found that this expansion was critically dependent on the presence of CD4 + T cells. Likewise, MHC-I-restricted CD8 + T cell proliferation responses to inactivated hepatitis B virus (HBV) Ags also were diminished by CD4 + T cell depletion [31], and, more recently, "effector" CD8 T cell expansion in response to HCMV was shown to be CD4 + T cell dependent [32]. We do not know whether CD4 + T cell help is required for cross-presentation in our system, but CD4 + T cells and/or IL-2 are required for memory CD8 + T cell expansion in response to whole HCMV ( figure 3 and figure 5A), and CD8 + T cell proliferation in response to the NLV9 HCMV peptide is minimal in the presence or absence of CD4 + T cells ( figure 4B and figure 5B).…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to observations in murine systems, we found that this expansion was critically dependent on the presence of CD4 + T cells. Likewise, MHC-I-restricted CD8 + T cell proliferation responses to inactivated hepatitis B virus (HBV) Ags also were diminished by CD4 + T cell depletion [31], and, more recently, "effector" CD8 T cell expansion in response to HCMV was shown to be CD4 + T cell dependent [32]. We do not know whether CD4 + T cell help is required for cross-presentation in our system, but CD4 + T cells and/or IL-2 are required for memory CD8 + T cell expansion in response to whole HCMV ( figure 3 and figure 5A), and CD8 + T cell proliferation in response to the NLV9 HCMV peptide is minimal in the presence or absence of CD4 + T cells ( figure 4B and figure 5B).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that some HBV-specific CD8+T-cell responses exist in chronic hepatitis [4][5][6], and their contribution was the control of the virus infection, which remained an important unresolved question.…”
Section: Introductionmentioning
confidence: 99%
“…Examination of HBV-specific T cells by limiting-dilution assays (7,56), proliferation assays (13,29,30,35), tetramer staining (46,58,69), and cytokine production has been limited to responses against predicted HLA-A2 epitopes of core, surface, and polymerase proteins and/or whole-antigen stimulation (2,46,49,64). In HIV-1 infection the dominant HIV-1-specific T-cell response is often to non-HLA-A2-associated peptides as well as to accessory proteins.…”
mentioning
confidence: 99%